Exploring Students’ Response in Reading Comprehension of Narrative Text through REAP (Read, Encode, Annotate, and Ponder) and Story Map Strategy - Nurul’aini, Ghina; Nugraha, Sidik Indra; Kartini, Dedeh (Journal of Educational Sciences, 2025)
English teachers should strive to create a living atmosphere in the classroom by carefully determine a proper strategy that supports the goal of the learning and entices students’ enthusiasm to learn more. The REAP and story map strategy are the two among several strategies that has been affirmed to improve students’ reading comprehension of narrative text. This present study aims to explore students’ attitudes regarding the joint-strategy of REAP strategy and story map strategy in assisting their reading comprehension of narrative text. A descriptive case-study design was used for this study and data obtained from the three instruments will be descriptively analyzed by using thematic analysis and measuring mean score of questionnaire results to interpret the data. Upon the data being analyzed, there are two major findings highlighted in the study. First, the two strategies used in the classroom involved cognitive processes such as critical thinking and motivation comes second following with students’ experiences at last. Second, students had positive attitudes toward the strategies used in the reading activity since they passionately participated in the drills. Specifically, these findings suggest that the mentioned strategies are appropriate to be applied in advancing students’ reading comprehension of narrative text.